Manajemen Dana Bantuan Operasional Sekolah (BOS) Dalam Perspektif Peningkatan Mutu Sekolah: (Studi Kasus Dana BOS Pada SMP Negeri 3 Penajam Paser Utara) - Hermanto, Sugeng; Hamid, Muliyadi; Rukaiyah, St (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2024)
This study aims to determine and analyze the Management of School Operational Assistance Funds (BOS) in the Perspective of School Quality Improvement (Case Study of School Operational Funds at SMP Negeri 3 Penajam Paser Utara). The research method used is qualitative descriptive with data collection through interviews, observation and documentation. Data analysis using field research. The results showed that the School Operational Assistance Budget (BOS) at SMP Negeri 3 Penajam Paser Utara has increased every year in accordance with the number of new student admissions at the school which has increased, this is in accordance with the Minister of Education and Culture Regulation No. 63 of 2023 concerning BOS juknis. In addition, there is self-help assistance from parents or guardians of students, the community, the business world in managing BOS funds and the management and use of BOS funds at SMP Negeri 3 Penajam Paser Utara is in accordance with the juknis.